Chapter 2 Protein Folding And Misfolding Deciphering Mechanisms Of Age-Related Diseases - Riemer, Judith-Elisabeth (Taylor & Francis, 2022)
Proteins are the key decision-making workforce for practically all cellular signals. The precise equilibrium between protein translation, folding, function and timely degradation, also known as "proteostasis", determine cellular health as well as organismal maintenance and survival. Loss of cellular proteostasis is linked with physiological processes of deterioration such as aging, with conditions characterized by supraphysiological oxidative stress as well as with illness, including age-related diseases, neurodegeneration, inflammation, dystrophies and cancer. This book includes 18 chapters logically organized to allow comprehensive understanding of how maintenance of proteostasis protects cellular and organismal health, and how environmental and metabolic pressure can impair proteostasis and lead to disequilibrium and disease. Each chapter contains up-to-date information on its respective topic while some of them review the interplay of certain proteostatic mechanisms, a newly arising topic. Importantly, most chapters include tangible examples of how failure of proteostasis can underlie aging and disease. We hope that the compilation of the above topics will assist both novice and experienced researchers and students to become more familiar with the subject of proteostasis. In the long run, we hope that this book will inspire its readers and eventually promote new ideas and new research studies.